علاقة الذاكرة العاملة بالمهارة اللغوية –قراءة و كتابة- وتأثيرهما في تحسين اللغة الشفهية عند الشخص المصاب بحبسة بروكا اقتراح بروتوكول علاجي - سليماني هدى (جامعة الجزائر 2, 2024)
The goal of this study is to investigate and identify the relationship relationship between working memory and linguistic skills (reading and writing) and their impact on improving oral language in individuals with Broca's aphasia. Our contribution centered on a pre- and post-study with the application of a proposed therapeutic protocol. We studied the pre and post correlation between working memory and linguistic skills (reading and writing), followed by an analysis of the differences statistically significant between pre- and post-tests of linguistic skills and working memory, and their impact on improving oral language in individuals with Broca's aphasia. The study sample included 22 patients with Broca's aphasia, intentionally selected. The methodology used was semi-experimental, suitable for this type of study. To validate our hypotheses, several tests were employed, In the statistical tools, we used Pearson's correlation coefficient to study the relationship and the t-test between two correlated samples (paired t-test) to examine the differences statistically significant. The results confirmed a significant positive correlation between the the working memory test and those of the written linguistic skills test. Furthermore, our study demonstrated the differences statistically significant between the pre- and post-test results for linguistic skills and working memory, indicating their impact on improving oral language in individuals with Broca's aphasia. In conclusion, these results enhance our understanding of the language improvement process in individuals with Broca's aphasia and pave the way for proposing indicators for therapeutic strategies and future research prospects.
Aucun
Keywords: مهارات لغوية; اللغة الشفهية; الذاكرة العاملة; علاقة; حبسة بروكا